Molecular identification of resistant genes in methicillin resistant Staphylococcus aureus among cardiac patients - Khan , Sherdil; Bashir, Kashif; Abbass Shah, Zafar; Ahmad, Ajaz; Amin, Faiz ul; Haqqani, Salima; Ullah, Amin (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Staphylococcus aureus, a prevalent cause of nosocomial and cardiac infections, particularly methicillin-resistant strains (MRSA), poses significant public health concerns due to limited treatment options. The current study of mecA and vanA genes confers resistance in S. aureus in Open Heart surgery patients. Methods: Among hundred clinical samples (pus) were processed tested for antimicrobial susceptibility, detecting MRSA using cefoxitin disc diffusion. Vancomycin Minimum Inhibitory Concentration (MIC) was determined, and chromosomal DNA was isolated for mecA and vanA gene analysis. Results: In this study, bacterial growth was found in 87% of the total specimens tested where S. aureus (68.9%) was the most common. All 60 S. aureus isolates were Penicillin-resistant, and the next most resistant antibiotics were erythromycin (96.6%), gentamicin (92.6%), while the highest sensitivity was shown by vancomycin (100%). MRSA was found in 70% of the sixty S. aureus. Out of 42 MRSA isolates, 4.7% were vancomycin intermediate Staphylococcus aureus (VISA) and the rest 95.2% were vancomycin sensitive Staphylococcus aureus. MRSA were not resistant to the drug vancomycin. The amplified mecA gene (167bp) was found in 61.6% (37/60) of the 60 S. aureus. None of the S. aureus strains possessed the vanA gene. mecA gene was found in 88.0% of 42 MRSA isolates and 100% of VISA isolates and five-methicillin-sensitive S. aureus (MSSA) were deficient in the mecA gene. Conclusions: High MRSA prevalence in cardiac patients increases antibiotic resistance, requiring expansion of diagnostic facilities and regular monitoring.